DIVERSITY OF TREES AND SHRUBS ON SPECIAL-PURPOSE FOREST - Silvani M Damanik; Luthfi Rahayu Ningsih; N Dwinur Rizki; Mieke Miarsyah (JURNAL PENA SAINS, 2019)
The beauty of KHDTK (Special-purpose forest) in Banten province saves a lot of biodiversities that must be protected because it is a source of wealth that supports human life towards prosperity. The research objective was to determine the diversity of trees and shrubs and to identify the types of plants (trees and shrubs) in the Forest Area with Special Purpose in Carita. This research was carried out in Sukarame Village, Carita District, Pandeglang Regency, Banten. The method used in this study is descriptive research. Technique sampling uses the Line transect method. The results showed that the tree Shannon-Weaver (H') Diversity index at KHDTK in Carita was 0.600 in the low category. Bush Shannon-Weaver (H) Diversity Index at Carita KHDTK is 0.692 in the low category. Evenness Index (E) at the KHDTK in Carita is 0.204 in the (low) category. The Evenness Index (E) in the Carita KHDTK was 0.33 in the low category. Further research is needed to be able to find diversity in the KHDTK in Carita and to complement references about KHDTK in Carita.